2012
DOI: 10.4018/jitpm.2012070103
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Project Management and Project Success

Abstract: One of the most important issues for organizations and information technology professionals is the success of information technology (IT) projects. This study reviews a survey of financial executives and examines their views on aspects of project management and project success. First, it was found that overall systems development projects are viewed as being successful by organizations. Next, a series of analyses were performed to assess several variables’ impact on IT project success. Skilled project measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…When the overall system development projects were viewed as being successful by the organization, skilled project management was cited as the reason for the successful project. Finally, a significant positive relationship was found between the IT project success and overall IT returns [14].…”
Section: Related Studiesmentioning
confidence: 99%
“…When the overall system development projects were viewed as being successful by the organization, skilled project management was cited as the reason for the successful project. Finally, a significant positive relationship was found between the IT project success and overall IT returns [14].…”
Section: Related Studiesmentioning
confidence: 99%
“…The organizational context that today's project managers must deal with in their everyday work situation is described by Ruuska and Vartiainen (2003, p. 307): "Today's organizations are often multi-project environments, where projects constitute a major part of business, and several project assignments are realized simultaneously". However, Peslak (2012) found that the size of the organization did not influence the IT project management success. Also Gillard and Price (2005) seem to have hit the head on the nail regarding the project managers' exposure by concluding that it is the project manager who is praised in times of success, but also the one who is blamed when things did not work out as well.…”
Section: Introductionmentioning
confidence: 92%
“…Although IT project success is important for the overall IT success [28], there are no formal criteria for project success. However there is a criterion that is stated very well by Iriarte and Bayona [25].…”
Section: Is/it Projectmentioning
confidence: 99%